2019
DOI: 10.7717/peerj.6648
|View full text |Cite
|
Sign up to set email alerts
|

Capacity for heat absorption by the wings of the butterflyTirumala limniace(Cramer)

Abstract: Butterflies can directly absorb heat from the sun via their wings to facilitate autonomous flight. However, how is the heat absorbed by the butterfly from sunlight stored and transmitted in the wing? The answer to this scientific question remains unclear. The butterfly Tirumala limniace (Cramer) is a typical heat absorption insect, and its wing surface color is only composed of light and dark colors. Thus, in this study, we measured a number of wing traits relevant for heat absorption including the thoracic te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 53 publications
0
8
0
1
Order By: Relevance
“…[ 70,71 ] Additionally, the high absorptance of BWs is helpful in absorbing heat from the sun to facilitate autonomous flight. [ 72 ] Different from moth eyes, opaque BWs can employ scattering structures with sizes much larger than the light wavelength. The typical ARS of black BWs are summarized below.…”
Section: Bioinspired Antireflective Microstructures (Ars)mentioning
confidence: 99%
“…[ 70,71 ] Additionally, the high absorptance of BWs is helpful in absorbing heat from the sun to facilitate autonomous flight. [ 72 ] Different from moth eyes, opaque BWs can employ scattering structures with sizes much larger than the light wavelength. The typical ARS of black BWs are summarized below.…”
Section: Bioinspired Antireflective Microstructures (Ars)mentioning
confidence: 99%
“…Others showed that the wings are used to regulate the body temperature of butterflies (e.g., Tsai et al, 2020 ; Wasserthal, 1975 ) and that climate change has favored light‐colored insects (e.g., Zeuss et al, 2014 ). The physiological mechanisms of heat transfer from the wings to the body were investigated, e.g., by Liao et al ( 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…The physiological mechanisms of heat transfer from the wings to the body were investigated, e.g., by Liao et al (2019).…”
Section: Introductionmentioning
confidence: 99%
“…This behavior enables butterflies to collect sufficient heat to maintain their body temperature. [ 23 ]…”
Section: Resultsmentioning
confidence: 99%